The Influence of Work-Life Balance on Employee Job Satisfaction at Bank Papua Teminabuan Branch - Hendra Setiawan; Susetyowati Sofia; Akmal Ridwan (IECON: International Economics and Business Conference, 2025)
This study investigates the impact of work-life balance (WLB) and quality of work life (QWL) on employee job satisfaction within a regional banking institution in Eastern Indonesia. The research aims to explore whether a supportive balance between professional and personal life correlates significantly with job satisfaction in the context of Bank Papua's Teminabuan Branch. quantitative research approach was applied using an associative-causal method. Data were collected through structured questionnaires distributed to all 33 employees at the branch, selected using a saturated sampling technique. The data were analyzed using multiple linear regression along with t-tests and F-tests to examine partial and simultaneous effects. The results demonstrate that both WLB and QWL significantly influence job satisfaction, both independently and jointly. Employees who perceive better balance and supportive working conditions report higher levels of satisfaction. The findings further suggest that improving WLB and QWL is essential in enhancing employee morale, commitment, and overall organizational performance. This study contributes to the limited body of research on employee satisfaction in peripheral regions, highlighting the critical importance of work-life policies in government-owned regional banks. The insights provided can support the development of human resource strategies tailored to improve employee well-being in similar institutional and geographic contexts